CHANNEL ALLOCATION METHODS FOR DIFFERENT FREQUENCY RANGE IN MOBILE COMMUNICATION - *, AASHIF (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
There is a growing demand for spectrum to accommodate future wireless services and applications. The present fixed allocation schemes have indicated a low utilization of the spectrum over both space and time. Hence, to satisfy the demands of applications it can be inferred that dynamic spectrum usage is a required necessity. According to the IEEE 802.22 standard the unlicensed secondary devices can operate in the licensed TV band, because this is the high underutilized licensed band, so long they do not interfere the licensed primary users. Therefore, the secondary users having cognitive radio features will automatically switch to another channel or mode upon detecting the primary user in its operating band. This paper is mainly concentrating on cognitive radio. Cognitive Radio is the fastest growing topic of research today. Undertaking the communication, what is the most important and precious natural resource? Radio Electromagnetic Spectrum. Various wireless applications require some bandwidth. Even with the most advanced technologies, radio spectrum allotted is limited. And even, the large portion of the assigned spectrum is used such that the geographical variations in the utilization of the allotted spectrum, ranges from 15% to 85% with high variance in time. That’s why we need some method for utilization of that wasted part. Cognitive Radio is just an approach of research to improve the utilization of this precious natural resource. What does it do to solve this problem? Sense the provide highly reliable communication for all users of the network and to facilitate efficient utilization of the radio spectrum in fair- minded way. spectrum holes available for employment by secondary users Radio Environment to detect the spectrum holesto The primary objectives of cognitive radio are